Glanzmann's thrombasthenia during pregnancy complicated by large subchorionic hematoma managed with antifibrinolytics, human leukocyte antigen-matched platelet transfusion, and primary cesarean delivery: a case report - Veronica Winget, MD, MS; Monique Schoenhage, MD, MBA; Teresa Orth, MD, PhD (Elsevier, 2022)
A 29-year-old primipara with Glanzmann's thrombasthenia presented for prenatal care at 8 weeks of gestation. Pregnancy remained uncomplicated until 22 weeks of gestation when a subchorionic hematoma, measuring 5.8 × 4.1 × 6.7 cm, was diagnosed and managed outpatient. At 28 weeks of gestation, the subchorionic hematoma was significantly expanding to 11 × 13 × 3.7 cm (∼30% of the placental surface). The patient was admitted for antepartum surveillance and steroid treatment. Fetal and maternal status were reassuring. At 36 weeks of gestation, there was active extravasation from the subchorionic hematoma, prompting interdisciplinary discussion with neonatal intensive care unit, blood bank, pharmacy, anesthesia, hematology, and the patient regarding her options. Immediate delivery risked platelet sensitization because of unavailable human leukocyte antigen-matched platelets. The patient opted for medical management with aminocaproic acid. At 37 weeks of gestation, she underwent a scheduled cesarean delivery. Human leukocyte antigen-matched platelets and additional aminocaproic acid were administered preoperatively. Intrapartum hemorrhage of 1200cc was controlled with uterotonics in addition to the above measures. Antifibrinolytics were continued. The neonate had an uncomplicated postpartum course. The patient had symptomatic anemia on postoperative day 1, which prompted red blood cell transfusion. Discharge was delayed until postoperative day 6 to further monitor her bleeding; oral antifibrinolytics were continued for 2 weeks. This case adds to the growing use of adjuvant medications, including antifibrinolytics such as aminocaproic acid and tranexamic acid, to reduce the reliance on platelet transfusion. This is critical for maintaining a favorable response to platelet transfusions and minimizing the risk of fetal neonatal alloimmune thrombocytopenia in current and subsequent pregnancies among women with lifelong bleeding disorders.